Hydrological assessment of basin development scenarios: Impacts on the Tonle Sap Lake in Cambodia. (1st February 2019) - Yu, Wansik; Kim, Yeonsu; Lee, Daeeop; Lee, Giha
Abstract: The study aimed to assess the hydrological impacts of the basin development scenarios—which are BS (baseline scenario), DFS (definite future scenario), and FFS (foreseeable future scenario)—by the Mekong River Commission (MRC) on the hydrological regime between the Mekong River and Tonle Sap Lake. The proposed CAESAR-LISFLOOD system was applied to analyze flood inundation patterns of the Tonle Sap Lake using satellite images, as well as to compare the simulated inundation maps. The flow duration variability was also analyzed at the outlet point of the Mekong River basin based on the analysis results of CAESAR-LISFLOOD, according to the basin development. The results show that the CAESAR-LISFLOOD model produces acceptable flooding areas (8607 km 2 ) compared with the satellite observations (9615 km 2 ), and the flood inundation areas decrease gradually from 3.69 (10 3  km 2 ) in the BS scenario to 3.54 (10 3  km 2 ) in the FFS scenario. However, it was found that the annual average flow duration variability scenario at the Kratie point, presented in the MRC, does not significantly affect the flow duration downstream from the Kratie point.